Development and applications of high-throughput SNP genotyping technologies in non-model plant genomes - Silva Junior, Orzenil Bonfim da (2017)
In the last twenty-five years, we have witnessed the wide adoption of DNA markers for the study of genetic variation in many organisms. A DNA marker must have two or more identifiable allelic DNA sequences to be useful. It usually does not have a biological effect, but instead functions as a traceable landmark in the genome, found in a specific location, and transmitted by the standard laws of inheritance from one generation to the next. Its application goes beyond genetic mapping and includes the analysis of genetic diversity, marker-trait association studies, marker assisted selection and, more recently, with the advent of wholegenome sequencing, whole-genome association and genomic selection. Among the several types of DNA sequence polymorphisms that can be used as DNA marker, Single Nucleotide Polymorphisms (SNPs) are the most powerful for large-scale variation analysis. There are vast numbers of SNPs in every genome and they can be typed by methods that have been proven easy to automate. Detection of alternative alleles is rapid and effortless because it is based on well-known polymerase chain reaction and DNA oligomer hybridization assays. Various strategies have been devised to discriminate alleles at a SNP, including fixed DNA arrays technologies, solution hybridization techniques and many sequencing-based genotyping. In our study, we have developed high-throughput DNA marker systems for non-model, highly heterozygous, diploid tree species. We took advantage of the combined power of Next Generation Sequencing (NGS) technologies, well-established highly automated methods of SNP typing and bioinformatics algorithms to perform genome-wide DNA variation analysis. We used whole genome resequencing of pooled individuals to develop a high-density 60K SNP chip for Eucalyptus species (EucHIP60k) providing a 96% genome-wide coverage with 1 SNP/12???20 kbp, and 47,069 SNPs at ??? 10 kb from 30,444 of the 33,917 genes in the Eucalyptus genome. We then used high-density SNP data and whole-genome pooled resequencing to examine the landscape of population recombination (??) and theta (??), assess the extent of linkage disequilibrium (r2) and build the highest density linkage maps for Eucalyptus to date. Chromosome-wide ancestral recombination graphs allowed us to date the split of Eucalytpus grandis (1.7???4.8 million yr. ago) and identify a scenario for the recent demographic history of the species. In a final set of studies, we built the first genome assembly for a Neotropical forest tree, the Pink Ip?? (Handroanthus impetiginosus), a highly-valued keystone timber species. Genome sequence was screened for the development of a targeted-capture sequencing system for SNP genotyping consisting of nearly 24,000 probe sequences. This genotyping system showed flexibility as it allowed the identification of SNPs across different populations of the species in moderate sample sizes. The good genome coverage, consistent Ts/Tv ratio estimated across samples and fair technical reproducibility between replicates, in terms of recall and precision of the SNP calling and accuracy on genotypes, indicate that this genotyping platform can be confidently used to estimate population genetics parameters and carry out population genomics investigations at the genome-wide scale